Worldwide transmission and seasonal variation of pandemic influenza A(H1N1)2009 virus activity during the 2009–2010 pandemic. Issue 6 (30th March 2013) - Storms, Aaron D.; Van Kerkhove, Maria D.; Azziz‐Baumgartner, Eduardo; Lee, Wing‐Kei; Widdowson, Marc‐Alain; Ferguson, Neil M.; Mounts, Anthony W.
<x xml:space="preserve">Abstract</x> Background Seasonal influenza activity varies with geography and time of year. Objective To describe how pandemic influenza A(H1N1)2009 [A(H1N1)pdm09] activity varied during the 2009–2010 pandemic. Methods We analyzed influenza virological data compiled by the World Health Organization from June 2009–August 2010. We calculated weekly proportions of A(H1N1)pdm09‐positive specimens out of all A(H1N1)pdm09‐positive specimens detected during the study period for each country. We compared parameters of pandemic activity (e.g., peak A[H1N1]pdm09 weekly proportion [peak activity], number of weeks between the 5th and 95th percentiles of A(H1N1)pdm09 cumulative weekly proportion [duration of activity]) between countries in temperate and tropical–subtropical regions. We quantified the proportion of A(H1N1)pdm09 out of all influenza A specimens by country and correlated it with countries' central latitudes. Results We analyzed data from 80 countries (47 temperate, 33 tropical–subtropical). The median proportion of cases identified during the peak week was higher in temperate (0·12) than in tropical–subtropical (0·09) regions (P < 0·01). The median duration of activity was longer in tropical–subtropical (27 weeks) than in temperate countries (20 weeks) (P < 0·01). In most temperate countries (98%), peak pandemic activity occurred during the fall–winter period. There was a positive correlation between country central latitude and proportion of A(H1N1)pdm09 out of all influenza A specimens (r: 0·76; P < 0·01). Conclusions The transmission of A(H1N1)pdm09 exhibited similarities with seasonal influenza transmission in that activity varied between temperate and tropical–subtropical countries and by time of year. Our findings suggest the potential utility of accounting for these factors during future pandemic planning.